Managing psychological issues among students with special needs in inclusive classrooms - Atteng, Catherine James (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2022)
This study is a peer into the management of psychological issues associated with students with special needs in inclusive classrooms. It examines disability and inclusive practices. The ways special educators might adapt their classrooms for young children with special needs were reviewed to include: supporting kids with impairments by providing other seating options is a terrific idea; rearranging the classroom's arrangement, particularly concerning the furniture, may also make it easier for kids with special needs to move about, visual clutter on walls might assist minimise distractions for kids with ADHD or autism, exciting the senses through mild music or white noise; etc. A flexible learning environment could be created by ascertaining their requirements and abilities, supporting, constructing a make-believe world, developing ties with the family, creating a sense of community, permitting treatments, and giving lessons in small groups. However, the education barriers for all students were found to include: negative attitude of parents, inadequate transportation infrastructure, poor level of engagement with the community, negative attitude of the teacher, insufficient teacher training, inadequate backing, classes number, education obstacles, cultural divide and understanding of the inclusive education idea is lacking. The ways to overcome the barriers were found to include: participation in studies on disability, case-study in complete inclusion, education of teachers and establishing an inclusionary culture. The main advantages of inclusion are that all kids gain when inclusion is done well because they can utilise some of the extra assistance. Supporting and promoting diversity and inclusion in the classroom is effective because it gives all students the chance to succeed and fosters an environment where students with special needs do not have to be separated from other students. Inclusion tackles misperceptions and unfavourable cultural attitudes toward those with disabilities or those who belong to minority groups.